Family planning programme and beyond: policy and administration - Goel, S.L. (New Delhi, 1990)
In this book, we have discussed the administrative components of the programme which are responsible to great extent for the success/failure of the programme. The effectiveness of family planning programme and population programme can be increased through the sound use of modern management techniques. The management of family planning programme can take the help of the various techniques for their purpose, c.g. 'systems approach of operational research, system analysis, programme budgeting, computer based information system; techniques concerned with the productive use of resources such as work study, network analysis and cost analysis and organisational and behavioural methods concerned with personnel selection, training, motivation, communication, adaptation to change, working in groups, the organisational development, management by objectives etc. Thus, the policy-makers and planners for family planning programme must also plan for effective implementation machinery to optimise the use of resources.
Keywords: Population control India